Urban PM2.5 Induces Cellular Toxicity, Hormone Dysregulation, Oxidative Damage, Inflammation, and Mitochondrial Interference in the HRT8 Trophoblast Cell Line - Nääv, Åsa; Erlandsson, Lena; Isaxon, Christina; Åsander Frostner, Eleonor; Ehinger, Johannes; Sporre, Moa K.; Krais, Annette M.; Strandberg, Bo; Lundh, Thomas; Elmér, Eskil; Malmqvist, Ebba; Hansson, Stefan R. (Frontiers in Endocrinology, 2020)
Objective Epidemiological studies suggest air pollution as a driver of adverse pregnancy outcomes such as low term birth weight, preeclampsia and gestational diabetes. The biological mechanisms mediating this correlation are largely unknown. To investigate the possible impact of urban particulate matter (PM) of size <2.5 μm (PM2.5) on placental function, a first trimester trophoblast cell line (HTR-8/SVneo) was exposed to various concentrations of PM2.5. Methods PM2.5 were collected at a site representative of urban traffic and dispersed in cell media by indirect and direct sonication. The HTR-8 cells were grown under standard conditions. Cellular uptake was studied after 24 and 48 hours of exposure by transmission electron microscopy (TEM). The secretion of human chorionic gonadotropin (hCG), progesterone and Interleukin-6 (IL-6) was measured by ELISA. Changes in membrane integrity and H2O2 production were analyzed using the CellToxTM Green Cytotoxicity and ROSGloTM assays. Protease activity was evaluated by MitoToxTM assay. Mitochondrial function was assessed through high resolution respirometry in an Oroboros O2k-FluoRespirometer, and mitochondrial content was quantified by citrate synthase activity. Results TEM analysis depicted PM2.5 cellular uptake and localization of the PM2.5 to the mitochondria after 24 hours. The cells showed aggregated cytoskeleton and generalized necrotic appearance, such as chromatin condensation, organelle swelling and signs of lost membrane integrity. The mitochondria displayed vacuolization and disruption of cristae morphology. At 48 hours exposure, a significant drop in hCG secretion and a significant increase in progesterone secretion and IL-6 production occurred. At 48 hours exposure, a five-fold increase in protease activity and a significant alteration of H2O2 production was observed. The HTR-8 cells exhibited evidence of increased cytotoxicity with increasing exposure time and dose of PM2.5. No significant difference in mitochondrial respiration or mitochondrial mass could be demonstrated. Conclusion Following exposure to air pollution, intracellular accumulation of PM may contribute to the placental dysfunction associated with pregnancy outcomes, such as preeclampsia and intrauterine growth restriction, through their direct and indirect effects on trophoblast protein secretion, hormone regulation, inflammatory response and mitochondrial interference.